2017
DOI: 10.1103/physrevb.96.100404
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the new efficient permanent magnet SmCoNiFe3

Abstract: Indeed, we find a correlation between the number of transition-metal (TM) 3d electrons and the stability of the hexagonal SmTM 5 (D2 d ) compound (TM = Fe, Co, or Ni), see Fig. 1 where we show results from calculations of formation energies. Notice that increasing the 3d electron count (more Ni) greatly stabilizes the compound. An obvious consequence of this behavior is that one should be able to recover crystal stability of a Sm-Fe alloy by doping with 3d electrons from nickel. We compare the theory with expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…Interestingly, a recent neutron diffraction experiment reported even larger local moments in SmCo 5 , which add up to give a resultant magnetization in excess of 12µ B /FU [73]. Studies employing DMFT and open-core calculations have reported smaller Sm total moments of approximately -0.3µ B , which would bring the total SmCo 5 moment closer to 8µ B /FU [49][50][51]. Earlier GGA+U calculations found a much larger total moment of 9.9µ B /FU due to a ferromagnetic alignment of Sm and Co spins.…”
Section: Comparison To Experimentsmentioning
confidence: 99%
“…Interestingly, a recent neutron diffraction experiment reported even larger local moments in SmCo 5 , which add up to give a resultant magnetization in excess of 12µ B /FU [73]. Studies employing DMFT and open-core calculations have reported smaller Sm total moments of approximately -0.3µ B , which would bring the total SmCo 5 moment closer to 8µ B /FU [49][50][51]. Earlier GGA+U calculations found a much larger total moment of 9.9µ B /FU due to a ferromagnetic alignment of Sm and Co spins.…”
Section: Comparison To Experimentsmentioning
confidence: 99%
“…An obstacle is the very limited equilibrium solubility of Fe in the SmCo 5 phase, which is metastable even without Fe addition. Other additives, such as Ti, Cu, Zr, Nb, and Ni, which were also considered from a very early stage [5,16,17,[18][19][20][21][22][23][24][25][26], often improve coercivity but tend to further reduce the magnetization and can therefore only be used in small amounts. A breakthrough occurred with the recognition that Co doping with Cu enhances the solubility of Fe and eventually leads to the formation of a high-magnetization Sm 2 (Co 1−x Fe x ) 17 phase surrounded by Sm(Co, Cu) 5 grain boundaries [3,16,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The practical disadvantage of this approach is the low remanence ratio of these essentially isotropic magnets, which overcompensates the magnetization gain due to iron addition, putting them at a competitive disadvantage compared to sintered Sm 2 Co 17 magnets. In fact, it was recently suggested [26] that the addition of Ni in Fesubstituted SmCo 5 stabilizes the 1:5 structure by adding 3d electrons.…”
Section: Introductionmentioning
confidence: 99%
“…For this terms we have derived an expression in terms of multiple scattering electronic structure theory, see Eq. (19) in the "Methods" section. Having Eq.…”
Section: Spin Interactionsmentioning
confidence: 99%
“…Having Eq. (19), it is easy to identify −2J ij δe i δe j and −2D ij δe i × δe j in Eq. 3with −2J * ij δe i δe j and −2D * ij δe i × δe j , respectively.…”
Section: Spin Interactionsmentioning
confidence: 99%